Breastfeeding is associated with waist-to-height ratio in young adults. (December 2015) - Bohr, Adam; Boardman, Jason; Domingue, Benjamin; McQueen, Matthew
Abstract Background The current study investigated the association between breastfeeding and adult weight distribution using an emerging indicator of weight distribution, the waist-to-height ratio (WHtR). Methods The study sample consisted of two subsamples of individuals that were part of the National Longitudinal Study of Adolescent Health. One sample (n = 1 179) consisted of individuals from the sibling pair data. A second sample (n = 4 648) consisted of individuals that were not part of the paired data. Regression models were constructed to establish if there was a relationship between breastfeeding and two measures of weight distribution: WHtR and body mass index (BMI). Controls for parental socioeconomic status, maternal smoking, race, sex, age, birth weight, maternal BMI, genetic ancestry, and a genetic risk score (GRS) for obesity were included. In addition, a behavioral risk score (BRS) was constructed to control for other residual confounding factors. Results A significant, inverse relationship between breastfeeding and adult WHtR persisted in models constructed from the sibling pair sample (P = 0.002) and unrelated sample (P <0.0001). This association remained significant with the inclusion of ancestry principal components, GRS, and a measure of maternal obesity. Conclusions The moderate association between breastfeeding and weight distribution persists into adulthood while controlling for potential confounders. This paper also provides evidence that the WHtR may be a superior outcome measure to BMI in studies investigating breastfeeding and obesity.